1, 2, 3, 6: Early Gothic Architecture and Perfect Numbers. Issue 1 (20th June 2014) - den Hartog, Elizabeth
Abstract : 'Knowledge of numbers should not be despised […] We are instructed in number to avoid confusion. Take away number in all things, and they all perish. Take away computation from the world, and all things are encompassed by blind ignorance; people who are ignorant of the knowledge of reckoning cannot be distinguished from the other animals'. Thus wrote Isidore of Sevilla in the 7th century (Book III, 4). Number clearly mattered. Indeed, the medieval world seems to have taken to heart the words expressed in the Book of Wisdom (11.21): 'Omnia in mensura et numero et pondere fecisti'. In such a number-obsessed world, one would expect number to play a significant role in the design of medieval architecture, for without number, a building, like everything else, would perish. And indeed, many medieval descriptions of buildings display a great concern with numerical values. After a short introduction into the issues involved, this paper will concentrate on the use of perfect numbers as a design principle in several select examples.